Standard specification for Seamless and Welded Steel Pipe for Low-Temperature Service (American Society of Testing Materials, 2005)
This specification is under the jurisdiction of ASTM Committee A01 on Steel, Stainless Steel, and Related Alloys and is the direct responsibility of Subcommittee A01.10 on Stainless and Alloy Steel Tubular Products.